Evaluación del comportamiento de los triglicéridos POP, POS Y SOS en la cristalización fraccionada y separación de una mezcla grasa para la obtención de CBE (2018)
The aim of this project was to evaluate the separation of a fat mixture by fractional crystallization in order to obtain a cocoa butter equivalent which can be beneficial for the food industry in a long term due to its similarity in the chemical composition with the cocoa butter. In the first part of the research, the significant variables of the process were highlighted trough preliminary tests and a literature review of scientific papers, degree works and patents. Therefore, it was necessary to make three experimental sets in order to: Model the separation of TAGs using solvents, evaluate the behavior of the fat mixture in front of a gradual and controlled cooling and design an experimental set up that simulates the equipment used at SIGRA SA plant. In this way, the importance of temperature, time and agitation in the fractionation was confirmed theoretically and experimentally. However, in the development of the experimental design, process variables were needed to guarantee the obtaining of two phases, for this reason a new variable called crystallization advance is proposed, which is an indirect measure of time and describes the time whereby it should be separated. Secondly, two sets were designed based on the preliminary tests and temperature ramps were developed.